PERFORMANCE, STRIDE CHARACTERISTICS, AND MUSCLE ACTIVITY WHILE RUNNING WITH A TRADITIONAL COMPARED TO A NEWLY DEVELOPED RUNNING SHOE (Kinesiology, 2018)
A new running shoe cushioning technology has been developed intending to dampen the landing impulse during running while allowing a powerful and direct push-off. We aimed to compare this newly developed technology to traditional running shoes in regard to endurance performance, spatiotemporal stride characteristics, ground reaction forces, and muscle activity. In a randomized crossover design, 13 recreational runners (age 24.9±1.2 years, height 1.68±0.07 m, body mass 62.8±6.0 kg, weekly running distance >30 km) were tested twice, once with their own traditional shoes and (with a 2-week run-in and a 6-week wash-out period) with shoes featuring the new technology. The two-day testing procedure consisted of a graded exercise running test to assess lactate threshold (LT) on day one. On the following day, muscle activity, ground reaction forces and spatiotemporal stride characteristics at two velocities (80% and 95% LT velocity) were recorded on an instrumented treadmill. Finally, 4 km time trial performance was assessed. Magnitude-based inferences were calculated to compare the two shoe conditions. Ground reaction forcewas likely higher at 95% LT (+5.7%) and possibly higher at 80% LT (+2.2%) with the newly designed shoes, while muscle activity was likely reduced in the tibialis anterior and biceps femoris muscles during push-off. Spatiotemporal stride parameters, physiological markers during the graded exercise test as well as time trial performance showed trivial or unclear differences between the conditions. The observed differences between the shoe conditions in ground reaction forces and muscle activity were insufficient to elicit improvementsin selected performance parameters.Key words: time trial, endurance performance, running biomechanics, EMG, running shoes